Brand Preference of Talcum Powder - Chidambaram, K.; Ganesan, S. (Indian Journal of Marketing, 2004)
Both men and women have been using cosmetics for thousands of years. Cosmetics are those articles which are intended to be rubbed, poured, sprinkled, or sprayed or otherwise applied to the human body or any part thereof for beautifying, promoting attractiveness, or altering the appearance. Cosmetics may cleanse the skin or change its colour, but they do not prevent or cure any dermal condition. Talcum powder is one of the popular cosmetics used both by men and women. It has been traditionally used for its fragrance and feeling of freshness.There are numerous companies marketing their talcum powder under different brand names. The major ingredients are more or less the same. However, the brand name of a product plays an important role in determining the product success or failure. Hence, an attempt is made to study the brand preference of talcum powder consumers. The study is undertaken with reference to Maduraites.